Darwin wasps of the subfamily Pimplinae (Hymenoptera: Ichneumonidae) of Mexico: Polysphincta genus-group - Khalaim, Andrey I.; Ruíz-Cancino, Enrique; Coronado-Blanco, Juana María (Zootaxa, 2024)
Mexican species of nine genera of the Polysphincta genus-group (Ichneumonidae: Pimplinae) are reviewed: Acrotaphus Townes (four species), Dreisbachia Townes (one species), Eruga Townes (four species), Flacopimpla Gauld (three species), Hymenoepimecis Viereck (two species), Oxyrrhexis Förster (one species), Polysphincta Grav. (seven species), Schizopyga Grav. (one species) and Zatypota Förster (four species). Two new species, Polysphincta sirena Khalaim, sp. nov. and P. xena Khalaim, sp. nov., are described and Eruga yehi Gauld, 1991 is found to be a junior synonym of E. lineata Townes, 1960 (syn. nov.). Two species, Schizopyga anseli Fernández-Triana, 2007 from Cuba and S. moreirae Loffredo & Penteado-Dias, 2008 from Brazil, are transferred to the genus Dreisbachia (comb. nov.). Three genera, Hymenoepimecis, Oxyrrhexis and Schizopyga, and ten species, Acrotaphus wiltii (Cresson), Eruga rufa Townes, E. straussi Gauld, Flacopimpla nigriceps (Walsh), Hymenoepimecis robertsae Gauld, H. tedfordi Gauld, Oxyrrhexis carbonator (Grav.), Polysphincta albipes Cresson, P. gutfreundi Gauld, Schizopyga circulator pulchra Walley and Zatypota crassipes Townes, are recorded for the first time from Mexico. Moreover, Dreisbachia avivae Gauld, Polysphincta purcelli Gauld, Zatypota alborhombarta (Davis) and Z. petronae Gauld are newly recorded from Guatemala, and D. avivae from USA. The male of Flacopimpla kasparyani Khalaim & Ruíz-Cancino is recorded for the first time. Identification keys to the species occurring in Mexico are provided.